2019
DOI: 10.1038/s41598-019-50568-4
|View full text |Cite
|
Sign up to set email alerts
|

Automated and Manual Quantification of Tumour Cellularity in Digital Slides for Tumour Burden Assessment

Abstract: The residual cancer burden index is an important quantitative measure used for assessing treatment response following neoadjuvant therapy for breast cancer. It has shown to be predictive of overall survival and is composed of two key metrics: qualitative assessment of lymph nodes and the percentage of invasive or in situ tumour cellularity (TC) in the tumour bed (TB). Currently, TC is assessed through eye-balling of routine histopathology slides estimating the proportion of tumour cells within the TB. With the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 18 publications
1
23
0
2
Order By: Relevance
“…Our second method that leverages feature extraction from the weakly-supervised segmentation mask yields the highest score among the all previously published feature extraction-based methods [24,19].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Our second method that leverages feature extraction from the weakly-supervised segmentation mask yields the highest score among the all previously published feature extraction-based methods [24,19].…”
Section: Resultsmentioning
confidence: 96%
“…Recent works by Akbar et al [24,25] have compared the conventional approach based on segmentation and feature extraction and direct applications of deep CNNs to image patches in both regression and classification settings. Overall, they showed that the DL-based approach outperformed hand-crafted features in both accuracy and intraclass correlation (ICC) with expert pathologist annotations.…”
Section: Related Workmentioning
confidence: 99%
“…Recent works by Akbar et al [3,2] have compared the conventional approach based on segmentation and feature extraction and direct applications of deep CNNs to image patches in both regression and classification settings. Overall, they showed that the DL-based approach outperformed hand-crafted features in both accuracy and intra- Figure 2: Encoder-decoder segmentation network architecture with Resnet-34 encoder and feature pyramid network decoder.…”
Section: Related Workmentioning
confidence: 99%
“…Breast cancer NAT therapy has been used as a locally treatment for breastconserving surgery [1], it provides prognostic and survival information [2] and is also used to determine a rate of local recurrence [3]. Efficacy of NAT is determined by means of the pathological complete response (pCR) but an accurate assessment of pCR is needed.…”
Section: Introductionmentioning
confidence: 99%
“…TC estimation problem was addressed by Peikari [10] who proposed a method based on nuclei segmentation and morphological parameters extraction used to train machine learning algorithms to classify cells as benign or malign. Akbar [1] compares this technique with deep learning and evaluates performance and also Pei [11] implemented a direct method based on transfer learning approach. Also during the 2019 SPIE Breast Path Q Challenge called for development of automated TC algorithms.…”
Section: Introductionmentioning
confidence: 99%